(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Recent experiments have provided scientific basis for the existence of multiverses - multiple physical universes located in space. String theory coupled with experiments with the quantum machine experiment further position multiverses not just as multiple universes in space, but also in time. While many papers have debated the scientific foundations for these concepts, few have evolved theories about the implications on earth of the existence of multiverses in space and time. In this paper, the author discusses the possible implications of multiverses due to pressure exerted by them in multiple dimensions. The author explores different effects of multiverses on physical phenomena experienced on earth such as earthquakes, volcanoes, and climate change, categorized by the levels of multiverse and the multiple dimensions in which pressure would be exerted.